Influence Perceived Attractiveness, Perceived Value to Revisit Intention with Satisfaction as A Mediation Variable in The Green House Lezatta Koto Hilalang Kabupaten Agam - Sinurat, Donal Anry Jaya (Yayasan Meira Visi Persada, 2024)
Currently the tourism sector is capable of becoming the fastest growing industry supported by the development of telecommunications and information technology globally. The high interest of people visiting various tourist attractions, especially in Agam Regency, can bring benefits and advantages to the surrounding community. The purpose of this study was to analyze the effect of perceived attractiveness (PA), perceived value (PV) on revisit intention (R) with satisfaction (S) as a mediating variable at the Green House Lezatta tourist attraction in Koto Hilalang, Agam Regency. This study was conducted in 2018 using a questionnaire and the sample introduction technique was convenience sampling. The population and sample in this study were 150 tourist respondents who had visited the Green House Lezatta tourist attraction. Data analysis with descriptive statistics and data processing using SEM (Structural Equation Modeling) with the Smart PLS version 2.0 program. The results of the study found that the influence of PA on S. PV on S and Ri. S to Ri, PV to Ri through S found positive and significant results, while PA to Si and PA to Ri through S had a negative and insignificant effect. The implication of this study is that tourism object managers must pay attention to visitor safety accommodation, offer a variety of cuisines, provide more attractive spots so that tourists want to return to the Green House Lezatta tourist attraction in the future.